Keser bojong: Idealisasi Pencitraan Jaipongan Karya Gugum Gumbira - Mulyadi, Edi; Ramlan, Lalan (LP2M ISBI Bandung, 2012)
Gugum GumbiraÃ¢â‚¬â„¢s Jaipongan as a dance genre has been more than ten repertoires, among oth- ers, are: Keser Bojong, Rendeng Bojong, Toka-Toka, Iring-Iring Daun Puring, Setra Sari, Senggot, Sonteng, Ringkang Gumiwang, Pencug Bojong, Rawayan, Kawung Anten, etc. However, among those works, Gugum Gumbira states his Keser BojongÃ¢â‚¬â„¢s dance repertoire as having the most ideal image. The question is, what aspects build that ideal image? Clearly, this is related to various value dimensions attributed to that dance repertoire. To discuss this issue, the writers use Richard E. PalmerÃ¢â‚¬â„¢s Hermeneutics as interpretation system to reveal the Ã¢â‚¬Å“hiddenÃ¢â‚¬Â meaning beyond the texts (1969: 16-31). The scope of discussion covers dimension of concept and dance construction as well as other artistic devices.Ã‚Â Keywords: Jaipongan, Keser Bojong, Image, Gugum Gumbira.Ã‚Â